MENENTUKAN WAKTU STANDAR PADA AKTIVITAS KERJA PRODUKSI SABLON MANUAL DI CV. DWIPUTRA IHWA - Dewanto; Yasmina Fajri Fajri; Muchtar, Diki Muchtar (Sekolah Tinggi Teknologi Wastukancana, 2024)
Standard production time analysis is one of the quantitative analysis method carried out to measure production time and aims to have a standard time as a planning reference before running production so that production time can be in accordance with the predetermined time limit. This analysis is carried out by calculating working time using a stopwatch on 6 (six) work elements, then a data sufficiency test is carried out which aims to determine whether the data needed is sufficient and suitable for analysis and a data uniformity test which aims to determine whether workers have good control while working. After the data is tested, the data is processed by determining the performance rating, calculating allowances and determining the cycle time as the time it takes workers to complete a job, normal time as the time to complete the work completed by workers under reasonable conditions and the standard time results as the output. The results of this study of 6 (six) elemen work, take mix 1- 3 colors from 15 , show that the standard production time of the manual screen printing by size 40 x 60 Cm at CV. Dwi putra Ihwa is 181.38 seconds or 3,023 minutes to complete a screen printing shirt in one cycle. Standard production time analysis is one of the quantitative analysis method carried out to measure production time and aims to have a standard time as a planning reference before running production so that production time can be in accordance with the predetermined time limit. This analysis is carried out by calculating working time using a stopwatch on 6 (six) work elements, then a data sufficiency test is carried out which aims to determine whether the data needed is sufficient and suitable for analysis and a data uniformity test which aims to determine whether workers have good control while working. After the data is tested, the data is processed by determining the performance rating, calculating allowances and determining the cycle time as the time it takes workers to complete a job, normal time as the time to complete the work completed by workers under reasonable conditions and the standard time results as the output. The results of this study of 6 (six) elemen work, take mix 1- 3 colors from 15 , show that the standard production time of the manual screen printing by size 40 x 60 Cm at CV. Dwi putra Ihwa is 181.38 seconds or 3,023 minutes to complete a screen printing shirt in one cycle.